Diverged Evolutionary Pathways of Two Public Research Institutes in Taiwan and Korea: Shared Missions and Varied Organizational Dynamics in ITRI and KIST. Issue 4 (2nd October 2021) - Wong, Chan-Yuan; Park, Sangook
Abstract: Industrial Technology Research Institute (ITRI) of Taiwan and Korea Institute of Science and Technology (KIST) of Korea are among the most acknowledged public research institutes in East Asia. This paper applies the evolutionary perspective for a comparative case study, emphasizing the path dependence with the innovation system context. Also, this paper elucidates the factors that configured the dynamics of ITRI and KIST in populating spin-offs and advancing biotechnology, respectively. It sheds new light on what particular organizational structures and routines would posit functionality in propagating certain activities and outcomes. The case of ITRI implies a strong mechanistic push in its organization to expedite its research activities and spin-offs. Meanwhile, KIST is endowed with patient capital and instituted service seniority in its career ladder, thus enabling it to develop science-based technologies and to evolve into a university-like institute. The structures and routines of the two PRIs are profound and productive in advancing their respective desired research agendas. However, their instituted routines might limit their pursuit of other kinds of growth ventures. This paper shows a depiction of organizational career ladders and spin-off mechanisms, which provides a useful guide for a government aspiring to construct similar structures and routines for certain outcomes.